Numerical modeling of metamorphic core complex formation: Implications for the destruction of the North China Craton - ZiQi Ma; Gang Lu; JianFeng Yang; Liang Zhao (Earth and Planetary Physics, 2022)
Widespread magmatism, metamorphic core complexes (MCCs), and significant lithospheric thinning occurred during the Mesozoic in the North China Craton (NCC). It has been suggested that the coeval exhumation of MCCs with uniform northwest-southeast shear senses and magmatism probably resulted from a decratonization event during the retreat of the paleo-Pacific Plate. Here we used two-dimensional finite element thermomechanical numerical models to investigate critical parameters controlling the formation of MCCs under far-field extensional stress. We observed three end-member deformation modes: the MCC mode, the symmetric-dome mode, and the pure-shear mode. The MCC mode requires a Moho temperature of ≥700 °C and an extensional strain rate of ≥5 × 10−16 s−1, implying that the lithosphere had already thinned when the MCC was formed in the Mesozoic. Considering that the widespread MCCs have the same northwest-southeast extension direction in the NCC, we suggest that the MCCs are surface expressions of both large-scale extension and craton destruction and that rollback of the paleo-Pacific slab might be the common driving force.